A Comparative Study Between Laparoscopic Subtotal and Total Cholecystectomy in Dogs - MIZUNO, NORIHITO; OKANO, SHOZO (Journal of applied veterinary sciences, 2025)
Open cholecystectomy (OC) is the standard treatment for canine gallbladder disease, but laparoscopic total cholecystectomy (LC) has recently been introduced as a minimally invasive alternative. In human surgery, laparoscopic subtotal cholecystectomy (LSC) is employed when Calot’s triangle dissection is difficult, but its efficacy in dogs remains unclear. We aimed to compare the surgical stress, biochemical changes, and perioperative outcomes of LC and LSC in clinically healthy dogs. Twelve healthy adult beagles were randomly assigned to LC (n=6; 3 male, 3 female, age 1.4 ± 0.2 y, BW 10.4 ± 0.9 kg) or LSC (n=6; 3 male, 3 female, age 1.5 ± 0.3 y, BW 10.5 ± 1.5 kg) groups. Operative time, serum C-reactive protein (CRP), white blood cell (WBC) and lymphocyte count, plasma cortisol, alanine aminotransferase (ALT), alkaline phosphatase (ALP), and total bilirubin (TB) were measured preoperatively and at multiple postoperative time points. Operative time was significantly longer in the LSC group than in the LC group (63.8 ± 14.2 vs. 34.7 ± 9.8 min, p < 0.05). Cortisol at 1 h postoperatively was lower in LSC, whereas CRP at day 7 was higher. Lymphocyte count at day 5 was higher in LSC, and WBC at day 7 was lower in LC (p < 0.05 for all). No significant intergroup differences were found in ALT, ALP, or TB, and no perioperative complications occurred. Although LSC resulted in a longer surgical time and higher CRP levels, it reduced cortisol levels in the early postoperative period and did not result in any significant intraoperative complications. Although these results were obtained using healthy beagle dogs, LSC may be an alternative to LC, especially when Calot's triangle dissection is difficult or there is a high risk of bile duct injury.